PREVALENCE OF BACTERIAL CONTAMINATION ON SMARTPHONE SURFACES AMONG OUTPATIENTS AT TRA VINH UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: Survey on the rate of bacterial infection and characteristics of bacteria isolated from smartphone surfaces of outpatients at Tra Vinh University Hospital.Methods: The cross-sectional descriptive study was conducted on 61 outpatients at the examination area of Tra Vinh University Hospital for 10 weeks (10–12/2022). Sample size 61, convenient sample selection. Bacteria are taken from the touch screen and the back surface of the smartphone with sterile cotton swabs, cultured and identified by biochemical tests. Data analysis using STATA 17.0 with Chi-squared, Fisher, and pre-existing ratio (PR) tests.Results: All smartphones (100%, 61/61) were contaminated with bacteria. Gram-positive bacteria predominated on both surfaces. Bacillus spp. were the most frequently isolated organisms on the touchscreen (91.8%) and the rear surface (93.44%), followed by coagulase-negative staphylococci (CoNS) (60.66% and 49.18%, respectively). The rear surface exhibited a higher prevalence of Gram-negative bacterial contamination (63.93%), including clinically important pathogens such as Escherichia coli and Pseudomonas spp. Smartphone cleaning was associated with a reduced prevalence of bacterial contamination on the touchscreen (PR = 0.64; 95% CI: 0.52–0.79; p = 0.018), whereas weekly or monthly cleaning frequency was associated with an increased risk of polymicrobial contamination. Proper hand hygiene was associated with a decreased risk of bacterial contamination on the rear surface (PR = 0.81; 95% CI: 0.70–0.94; p = 0.041).Conclusion: Outpatient smartphones are a potential source of bacteria, especially on the back surface. It is necessary to strengthen smartphone hygiene combined with proper hand hygiene to limit the spread of bacteria.
Keywords: Bacterial Contamination, Smartphones, Outpatients